PEDAGOGUE TECHNICAL UNIVERSITY 21ST CENTURY: SEARCH INNOVATION MODEL - Лузік, Ельвіра Василівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article the relevance of research training problems harmonious personality technical university lecturer in the modernization of higher technical education, able to operate successfully in a changing dynamic information space. Based on the analysis of core competencies that should have Lecturer Technical University 21, namely competence scientist and researcher, information, language, adaptive, communicative, ability to learn throughout life, stressed the need for modernization of the educational activities of the teacher of higher technical education by integrating traditional teachers and new information and communication technologies training